26. Karelian in Russia: ELDIA Case-Specific Report - Kovaleva, Svetlana; Karjalainen, Heini; Grünthal, Riho; Puura, Ulriikka
Report on the case study on the Karelian language in Russia, conducted within the EU-FP7 research project ELDIA